2017
DOI: 10.1093/ageing/afx121
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in older patients with acute coronary syndrome randomised to an invasive or conservative strategy. The After Eighty randomised controlled trial

Abstract: NCT01255540.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 34 publications
0
10
0
2
Order By: Relevance
“…Wahrborg et al [33] found similar scores of QoL in patients with and without therapeutic strategies. Tegn et al [48] also found no statistically significant difference in QoL score between invasive strategy (IS) and conservative strategy (CS) treatments in all domains except for bodily pain.…”
Section: Changes In Qol Among Acs Patients After Treatmentmentioning
confidence: 95%
See 1 more Smart Citation
“…Wahrborg et al [33] found similar scores of QoL in patients with and without therapeutic strategies. Tegn et al [48] also found no statistically significant difference in QoL score between invasive strategy (IS) and conservative strategy (CS) treatments in all domains except for bodily pain.…”
Section: Changes In Qol Among Acs Patients After Treatmentmentioning
confidence: 95%
“…Upon further critical appraisal through peer review, seven articles which assessed the secondary outcome were excluded as (i) the outcome of interest was not measured before and/or after treatment (5), (ii) outcome compared between ACS and non-ACS (1), and (iii) ACS patients who also had chronic kidney disease (1). Finally, 29 studies were included for review of which 16 studies [15,28,29,33,[39][40][41][42][43][44][45][46][47][48][49][50] assessed disease specific QoL and 13 studies [26,[51][52][53][54][55][56][57][58][59][60][61][62] assessed generic QoL. Of these studies, 13 studies were RCTs, 12 were cohort studies, two were cross-sectional studies, and two were reviews.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The superiority of the invasive strategy was diluted with increasing age, and was not reflected by changes in health-related quality of life, as measured by the SF-36. 4 Here, we report the angiographic and procedural results of the After Eighty study. Analysis was performed to identify independent predictors of revascularisation.…”
Section: Introductionmentioning
confidence: 98%
“…The superiority of the invasive strategy was diluted with increasing age, and was not reflected by changes in health-related quality of life, as measured by the SF-36. 4 …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the vascular interventional therapy for lower extremities has developed rapidly in China. However, there are some deficiencies in the preoperative evaluation of patients and the control of postoperative metabolic indices, accompanied by short follow-up period, small sample size and low success rate of surgery [2]. In this study, therefore, the therapeutic effects of interventional therapy and conservative therapy on ASO were compared, and the risk factors for prognosis were analyzed, aiming to provide a valuable evidence for clinical treatment.…”
Section: Introductionmentioning
confidence: 99%